Can the county to district reform in China restrain corporate earnings management? From the perspective of regional local protection - Shasha Liu; Huixian Zhao; Gaowen Kong; Dongmin Kong (China Journal of Accounting Studies (CJAS), 2023)
Under the strategic background of regional coordinated development, the County to District can remove administrative barriers and reduce local protection. Based on the matching data of Chinese A-share listed companies from 2000 to 2018 and the County to District Reforms, this paper empirically explores the influence of County to District Reforms on earnings management. We find the County to District Reform can effectively reduce earnings management, especially in areas with high local protection. Further mechanism analysis shows the County to District Reforms reduce local protection by increasing credit availability for enterprises, and ultimately restrain earnings management. Additional analysis shows the County to District Reforms increase the bank loans of enterprises in areas with higher local protection. This paper deepens the understanding of the County to District Reforms and enriches the literature on how government actions can affect corporate governance.
Keywords: 650; The county to district reform; earnings management; local protection; credit availability